2014
DOI: 10.4236/ojra.2014.44031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Attitude in a Sample of Patients with Rheumatoid Arthritis and Its Association with Disease Activity and Severity: A Cross-Sectional Study

Abstract: Background: Rheumatoid arthritis (RA) is a chronic and disabling disease that has a major impact on the lives of patients. Objectives: To test the patients' knowledge about their disease, its treatment, its complications, and if this affects severity of the disease as measured by the disease activity index (DAS 28). Patients and Methods: A sample of 100 patients with RA who met the Criteria of American College of Rheumatology for RA agreed to participate in this study over the period September 2011-March 2012.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The outcomes of this study revealed that the participants' understanding of RA was lacking. In contrast, communities in Egypt, Iraq, Netherlands, and Portugal showed higher knowledge of the condition, with more than half of the research participants knowing of RA [ 15 - 18 ]. The analysis showed that the participants received a mean score of 2.06 out of 15 items regarding general knowledge of RA.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of this study revealed that the participants' understanding of RA was lacking. In contrast, communities in Egypt, Iraq, Netherlands, and Portugal showed higher knowledge of the condition, with more than half of the research participants knowing of RA [ 15 - 18 ]. The analysis showed that the participants received a mean score of 2.06 out of 15 items regarding general knowledge of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) may slowly progress over time, which sometimes proves difficult for a patient to manage. Many studies conducted in different geographical places of the world have emphasized the need for patient-oriented disease awareness and education [ 6 , 8 , 9 ]. There is a scarcity of literature concerning RA in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the UK exhibited good knowledge about diagnosis and treatment but lacked knowledge related to the adverse effects of drugs [ 7 ]. Evidence from the region around Pakistan indicated that the knowledge of Iraqi and Pakistani patients was quite low [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may have a certain amount of knowledge and concept or their understanding about their disease, but this may be fl awed or overestimated and can never fully or get balance with the expertise of the medical consultation. Overestimating their knowledge about their illness could have two eff ects on patients: it may decrease their motivation to learn more about their condition because by their assessment they already know enough about their illness and have the best knowledge to manage it, and it may lead them to make choices about their health independently [24]. Patients may have multiple views, by careful collection, these views are tried to be more directed and specifi c, and by a discussion of the consequences of chronic illness on patients and the possible role of the level of knowledge, by all of these, patient's understanding of chronic AS illness and its experience will be deepened.…”
mentioning
confidence: 99%